Fodder production responses to prunning height and fodder quality of some trees and shrubs in a forest-savanna transition zone in southwestern Nigeria - Larbi, Asamoah; Awojide, A.A.; Adekunle, I.O.; Ladipo, D.O.; Akinlade, J.A. (Springer, 2000)
Seasonal fodder production responses of five shrubs (Centrosema arenarium, Desmodium strigillosum, Desmodium velutinum, Phyllodium pulchellum, and Tadehagi triquetrum) and five trees (Albizia gummifera, Berlinia grandiflora, Albizia niopoides, Bauhinia monandra, and Inga edulis) to pruning heights ranging from 15 to 75 cm were evaluated during the main-wet, minor-wet, and dry seasons of 1993 and 1994 in the forest-savanna transition zone of West Africa. Fodder from the main-wet season was analysed for nitrogen (N) and phosphorus (P), and dry matter degradation characteristics after 6, 12, 24, 48, 72 and 96 h of incubation in rumen-fistulated N'Dama steers. In the minor-wet season, fodder production of all species increased in response to increasing pruning height with the exception of pulchellum and A. gummifera. Highest fodder production was attained at a pruning height of 45 cm for the Desmodium species, 50 cm for pulchellum, and 75 cm for the rest of the species. Concentrations of N and P varied significantly among the species; for N the ranges were 28.7-38.8 g kg-1 (shrubs) and 25.3-44.5 g kg-1 (trees), while for P the ranges were 3.26-7.04 g mg-1 (shrubs) and 3.58-6.76 g mg-1 (trees). Dry matter degradation characteristics differed significantly among shrubs and trees; ranges for shrubs were: soluble fraction (a), 128-185; degradable fraction (b), 664-703; potential degradability (PD), 793-857, as g kg-1; rate of degradation (c), 0.0241-0.0308 as percent h-1 while for trees ranges were: (a), 139-160; (b), 651-826; (PD), 824-970, as g kg-1; (c), 0.0143-0227 as percent h-1. Based on fodder production and quality, C. arenarium, D. strigillosum, D. velutinum, B. monandra, I. edulis, and A. niopoides were the most promising species for the development of animal agroforestry technologies in the west African forest-savanna transition zone and similar environments in the tropics.